An Interplay of Academic Procrastination, Achievement Goals, and Personality Traits among Students: Evidence from South Punjab, Pakistan - Khan, Marvi; Bashir, Asma; Bibi, Hafiza Shahzeena (The Regional Tribune, 2026)
Academic procrastination is a common problem, but little research has been conducted on its relationship with personality traits and motivation in non-Western countries. This study investigated these correlations in Pakistan, utilizing a sample of 500 Pakistani university and vocational students. Employing the correlational design, the participants took part in the Big Five Inventory, Achievement Goal Questionnaire-Revised and Academic Procrastination Scale. The results demonstrated that the achievement goals had a positive but weak correlation with extraversion, agreeableness, and conscientiousness, and no correlation with neuroticism. Academic procrastination correlated negatively with extraversion, agreeableness, conscientiousness and openness and correlated positively with neuroticism. Further regression analyses found that conscientiousness, neuroticism and achievement goals collectively predicted academic procrastination. Moreover, moderation analysis found that moderate-to-high achievement goals attenuated the relationship between personality and procrastination, indicating that they acted as buffers. There were no gender differences, but the vocational students had higher achievement goals than university students. The current research expands personality and motivation research into Pakistani culture, demonstrating that achievement goals need to be developed in order to prevent procrastination.